Amazonian cask-body: rituals of animation and celebration in the nugget city (Móin-Móin Magazine - Studies in the Art of Puppetry, 2026)
colonial rite that merges body, living costume, and territory into a single animated entity. It introduces the concept of the Amazonian mask-body as a living sculpture and critical device that turns animation theatre into a gesture of purification, denunciation, and insurgent celebration. The practice-based research positions the Amazon as an epistemological and communal field of poetic and political resistance.
Keywords: body-mask; Amazonia; animation theatre; ritual; community